Plan de negocios para la producción y comercialización de arepas nutritivas en el municipio de Villamaría (2013)
The idea of designing a business plan for production and marketing of nutritional arepas in Villamaria begins at the Alto del Portón neighborhood, where is evident the lack of ownership in a small business dedicated to the production of arepas, and that merely grows, due to habit of the traditional process. These becomes a disadvantage for the development and commercialization of arepas and also the deficient financial control do not allow the business to identify the need to be trained on how to take the business and know and improve their profitability. Being aware of this situation not only in this case but in other arepa businesses of this size becomes evident that there is a need of a company in Villamaria to exercise appropriate administrative processes and innovation in the production, development and product presentation. This project aims to implement actions to help improve the development of financial, administrative, organizational, marketing, and social work with the environment; also introducing the market a product that besides its nutritional supplement, is creative in its design and presentation which gives an elegant and additional attractive to the product, and also contributes to the conservation of the environment, because their packaging is biodegradable unlike other similar products that do not have environment benefits. To identify the needs of consumers in the town of Villamaria, a descriptive study was used, which collects data based on observation, interviews and questionnaires to employers and through deductive research method, so they can gain knowledge through an analysis of the food industry.